Carotid Artery Doppler Study in Patients Presenting with STEMI: Carotid Artery Doppler Study with STEMI - Khan, Owais; Khan, Tashfeen Irtaza; Hussain, Cheragh; Ali, Yamna (Pakistan Journal of Health Sciences, 2025)
Carotid Artery Disease (Carotid CAD) is a significant risk factor for cardiovascular events, particularly in patients with ST-Elevation Myocardial Infarction (STEMI). Carotid artery stenosis (CAS) has been related to poor outcomes in STEMI patients, but limited data exist on the prevalence and severity of CAS in this population, especially in Pakistan. Objectives: To evaluate the presence, severity, and characteristics of Carotid CAD through Doppler ultrasonography in STEMI patients, and to assess the relationship between CAS and clinical outcomes such as hospital stay duration. Methods: A cross-sectional observational study was conducted at Hayatabad Medical Complex, Peshawar, from May 2025 to August 2025. A total of 172 patients with STEMI were assessed using a Mindray® DC 70 Colour Doppler Ultrasound Scanner. The severity of CAS was classified as mild, moderate, or severe based on Peak Systolic Velocity (PSV). Results: The study found that 48 (27.9%) patients had mild CAS, 86 (50%) had moderate stenosis, and 38 (22.1%) had severe stenosis. The mean PSV values were 95.3 cm/s (mild), 123.4 cm/s (moderate), and 142.8 cm/s (severe). Patients with severe stenosis had significantly longer hospital stays (mean 9.2 days) compared to mild (6.3 days) and moderate stenosis (7.5 days); the p-values obtained were 0.025 and 0.035, respectively. Hypertension showed a significant association with severe stenosis (p = 0.016). Conclusions: This research work highlights the high prevalence of CAD in STEMI individuals.